Uji Kepadatan Tanah Timbunan Pilihan Untuk Inti Bendung Terhadap Nilai Permeabilitas - Anggraini, Hany Octavia; Iswan, Iswan; Afriani, Lusmeilia (Universitas Lampung, 2021)
The development of infrastructure development in Indonesia is increasing in various areas, such as the construction of reservoirs, reservoirs, dams and other constuctions. One of the important things that is the basis of development is land because almost all buildings stand on the ground. Therefore, it is necessary to know the type of soil used and the nature of the soil permeability. Soil permeability describes the ability of the soil to pass water. Soil samples used were soil samples from Pamenang village, Pagelaran sub-district, Pringsewu district. Soil samples taken are disturbed and undisturbed soil samples. The soil is then compacted by the standard method and with the pressure method test apparatus at a pressure of 2,5 MPa, 5 MPa, 7,5 MPa, 10 MPa, 15 MPa, 20 MPa, and 30 MPa, each method has one sample being tested. Furthermore the permeability test was carried out to obtain the permeability coefficient value.Results from observations in the laboratory show that the greater the pressure exerted on the soil, the smaller the permeability coefficient. The relationship between the permeability coefficient and the standard compaction method and the pressure method obtained different permeability coefficient values.Keyword : Soil, Compaction, Pressure and Permeability